Pengembangan Aplikasi Game dengan Html5 dan Javascript untuk Mengukur Kecerdasan Anak - Ismail, Muhammad (Bina Nusantara University, 2014)
Educational games are the ideal medium to see the extent to which a student's performance will be assessed. However, to integrate educational games has the technical and practical challenges of their own. This study will be directed to the development of a game that can be used to measure the kind of intelligence and capabilities of a child based on the reference of Psychology Howard Gardner's theory kuisinoerThe purpose of writing is the development of gaming applications with HTML5 and JavaScript enabled to measure intelligence. The data taken from the distribution of questionnaires to 30 respondents were randomly. The data were analyzed by finding the average difference between the results of tests using questionnaires to play the game. From these results it can be concluded that there is a gap/difference between the average differences among the results of the two tests.